2019
DOI: 10.4236/ajac.2019.1010035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality Parameters of White and Brown Eggs in Lebanon

Abstract: The quality traits of fresh marketable chicken eggs collected during winter, autumn and summer periods from different local markets in Lebanon were evaluated in order to understand the reproductive fitness of the chicken and the correlation between collection dates. A total of 2000 brown and white eggs were analyzed and compared for their external quality parameters such as egg weight, length, width, size, shell thickness, specific gravity and for their internal quality traits such as Haugh unit, yolk diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Shell strength was under no influence neither of strain nor the storage which is in line with the results reported by Jones and Musgrove (2005). Joubrane et al (2019) found no significant differences in shell quality between brown and white shell eggs. Contrary to our results, Đukić Stojčić et al (2017) found that shell strength significantly decreased during storage.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Shell strength was under no influence neither of strain nor the storage which is in line with the results reported by Jones and Musgrove (2005). Joubrane et al (2019) found no significant differences in shell quality between brown and white shell eggs. Contrary to our results, Đukić Stojčić et al (2017) found that shell strength significantly decreased during storage.…”
Section: Resultssupporting
confidence: 90%
“…Silversides and Scott (2001) found that eggs from ISA Brown were larger than eggs from ISA-White. Larger egg size in brown hens compared to white hens was also reported by Vits et al (2005) and Joubrane et al (2019). These authors assumed that genotype has a direct influence on egg weight and other egg characteristics.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In commercial egg industry, egg quality is the best endorsed by routine egg grading practices. Grading of eggs is mainly performed based on the egg weight and the quality of eggshell, albumen, yolk, and the air cell (Stadelman, 1995;Joubrane et al, 2019). It is well known…”
Section: Introductionmentioning
confidence: 99%
“…Figure3: Egg weight loss according to the level of sour starfruit during storage time occur morequickly. The longer the ST, the supply of liquids and gas will shrink or decrease( Joubrane et al, 2019). Applying 20% SSF extract storage at room temperature for six weeks was the best treatment.…”
mentioning
confidence: 99%